Literature Review: Semantic Roles – The Agent in “The Little Prince” Book by Antoine de Saint-ExupéryREVISI, MINIMAL 8 HALAMAN - Nadiya Salsabila, Shalsa Sirfia Dewi (Integrative Perspectives of Social and Science Journal, 2025)
This article explores the use of semantic roles, specifically the role of the Agent, in Antoine de Saint-Exupéry’s The Little Prince. The study aims to identify and analyze how the Agent role is realized in various sentence structures throughout the novel. As the initiator of an action, the Agent plays a central role in understanding who performs what action in a clause. The research applies a qualitative descriptive method, using semantic role theory proposed by Kroeger (2005) and Dowty’s Proto-Role theory (1991) as the analytical framework. The data consist of selected sentences from the original English version of the novel that include transitive or intransitive verbs, where semantic roles can be clearly assigned. Each sentence is examined to identify the predicate (verb), the arguments related to the action, and the specific role of the Agent. The findings show that the little prince is the most frequent Agent in the novel, representing his function as the main character who initiates actions, makes decisions, and drives the plot forward. Other Agents include the pilot, the fox, and the rose, each fulfilling different narrative roles. The study also reveals that Agent roles are not limited to human or animate subjects, but can also be metaphorically assigned to objects or concepts depending on the context. This investigation further incorporates psycholinguistic insights (Kretzschmar et al., 2019), considering how readers process and assign agentivity in contexts where syntactic cues are minimal or ambiguous. Such perspectives reveal how linguistic structures in The Little Prince guide readers’ cognitive framing of responsibility and action. Computational studies on semantic role labeling (Gildea & Jurafsky, 2002; Titov & Khoddam, 2014) are also referenced to demonstrate how advances in automatic analysis can complement manual qualitative approaches for literary texts. In conclusion, this article demonstrates that analyzing Agent roles in a literary text provides valuable insight into character dynamics, thematic structure, and narrative development. This approach can enrich the interpretation of literary works by revealing how meaning is constructed through language and grammar.